Implementasi MQTT Websocket Pada Sistem Pendeteksi Detak Jantung - Alfrienza Tighfaraka Alifibioneri; Heru Nurwarsito; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The development of the IoT (Internet of Things) technology era, the heart rate detection system can be integrated with the internet network, which can be accessed by the web or certain applications, so that heart rate monitoring is carried out more easily and efficiently. Hardware integration which includes Pulse Sensor, Wireless Transmission Module (ESP 8266 Module), Raspberry 3B and Arduino. 0.6% performance for sensor error rate and data transmission capability with packet loss <1% for ESP modules. The MQTT protocol is often used mainly because of low power consumption, low bandwidth, high scalability and very low overhead. This system will send data related to the heart rate that has been obtained to the server to be processed. After that, the data will be sent to the user's application in real-time. In connection with that, from the aspect of networking in the application of IoT on the system using QoS as a measurement method In this study using a pulse sensor that is placed on the wrist or fingertip to obtain heart rate data in bpm units, then the data is sent using MQTT to the Raspberry PI broker used, and users can access the website to view real heart rate data real-time. QoS Test Results for Delay parameters in heart rate data transmission using the MQTT protocol are classified as very good, resulting in QoS delay level 0 of 1.44 ms, QoS level 1 of 2.06 ms and QoS 2 of 2.35 ms. QoS for the Throughput parameter in heart rate data transmission uses the MQTT protocol for each data transmission with an average QoS level 0 of 930 kbps, QoS level 1 of 757 kbps and QoS 2 of 504 kbps. QoS for Packet Loss parameters in heart rate data transmission using the MQTT protocol is very good, resulting in packet loss of less than 1% with all QOS levels tested not finding packet loss.